COMMUNICATION LEVELS OF THE INDIVIDUAL - V. M. Rubskyi (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
Purpose. The article deals with the problem of mutual perception of individuals, which implies the analysis of the anthropological prerequisites for the study of interpersonal communication. The work emphasizes the need to identify the gnoseological lacuna of the possibility and relevance of knowing someone else’s "I". As well as the need to point out implicit metaphysical attitudes, universal for many worldviews, which are implicitly included in the theory of personal communication. Theoretical basis. The author proceeds from the logical consequences of the evolutionary premise in anthropology. He compares the psychophysical goals of the interpersonal communication task with its ideological theory, monitors the impossibility of the realizing the communication level declared in the consciousness. As an opposite evolutionary premise, the author cites the postulates of the "philosophy of dialogue" by F. Rosenzweig, F. Ebner, M. Buber, and others. The correlation of these philosophical positions reveals the inconsistency of materialistic reduction in anthropology. Originality. The author identifies four levels of communication: background, obstacle, function and dialogue. He represents the rationale for the fact that the first three levels do not need the existence of an individual "I". The first three levels leave the existential "I" unnecessary and therefore unclaimed. The philosophy of dialogue with the Other raises an equally important question about the conditions for the possibility of a metaphysical continuum in ontology, and in turn, suggests the acceptance of a philosophical premise about God as the space of subjectivity in the "I-You" dialogue. Conclusions. Philosophical understanding of the communication of two existential "I" demanded in communication is possible only within the framework of religious discourse. The phenomenal consciousness can enter into communication with a specific other phenomenal consciousness only when there is a metaphysical space between them, allowing for the possibility of communication of such a level. The materialistic conditioning by the human evolutionary needs in all its conceivable forms produces a reduction of the communicative inquiry, which makes the mutual perception of the two "I" impossible. In this psychophysiological anthropological model, there is no space for the possibility of a dialogue of individuals.